Informal land access for housing and associated settlement developments in Bahir Dar City, Ethiopia - Adigeh, Dereje Tessema; Mekuria, Endale Belay; Abebe, Birhanu Girma (Frontiers in Human Dynamics, 2025)
Bahir Dar city, a rapidly urbanizing city in Ethiopia, faces acute housing and urban land demand, resulting in the prevalence of informal land acquisition and housing development. Therefore, this study aims to examine the informal land acquisition for housing in Bahir Dar, resulting in informal settlement expansion, focusing on the conditions, contributing factors, participants, and procedures of informal land transaction settlements. Data were collected by interview from purposefully selected key informants, including land sellers, buyers, brokers, urban land administrators, and code enforcement officers, supplemented by field observations and desk reviews. The study reveals that informal land transactions are the primary means of urban land acquisition for housing in Bahir Dar city, especially in peri-urban rural expansion areas, because the formal system of land access lags far behind. The key causes for this are high urbanization rates, inefficient urban land administration, which fails to supply formal residential plots, and low compensation payments to peri-urban landholders. Peri-urban farmers are the leading land sellers, inner-city residents in rental homes are the primary buyers, and brokers facilitate the transactions, with local administrators often legitimizing informal acquisitions. The study recommends that the government improve the efficiency of formal urban land supply and provide affordable housing to alleviate informal land developments and settlements.